A QUALITATIVE STUDY OF FIXED ASSET ACCOUNTING INFORMATION SYSTEM AT PT HASJRAT ABADI MANADO - Fillycia Imanuela Samuri; Opa Mustopa; Anneke Marie Kaunang; Siti Mariam (Yayasan Adra Karima Hubbi, 2026)
This study analyzes the implementation of a fixed asset accounting information system, PSAK 16 conformity, and COSO-based internal control at PT Hasjrat Abadi Manado Branch. The study aims to examine how the system supports asset recording, coding, depreciation, reporting, monitoring, and decision-making in the management of equipment assets. A descriptive qualitative approach was used because the research focuses on field-based procedures, control practices, and operational constraints rather than statistical hypothesis testing. Data were collected through interviews, observation, and documentation, then analyzed through data reduction, data display, conclusion drawing, and triangulation. The findings show that SBO or SAP Business One has been used since 2014 and has improved six main process areas: asset acquisition recording, asset coding, acquisition cost recording, depreciation calculation, asset location tracking, and report preparation. Based on qualitative benchmarks from field evidence, recording, coding, reporting, and data retrieval were relatively strong, while depreciation accuracy, disposal timeliness, and monitoring remained moderate because they depend on correct asset classification, document completeness, and physical verification. The main weaknesses include input errors, delayed supporting documents, non-real-time updates, annual-only physical inspections, and the absence of automatic reminders. These weaknesses may delay maintenance, replacement, and disposal decisions and may reduce the reliability of asset information. The novelty of this study lies in its integrated analysis of fixed asset accounting information systems, PSAK 16, and COSO-based internal control at the branch level. The findings imply that stronger validation, more frequent physical inspection, real-time updates, and better branch–head office integration are needed.